MTS1338 in Mycobacterium tuberculosis promotes detoxification of reactive oxygen species under oxidative stress. (December 2021) - Singh, Saumya; Nirban, Reena; Dutta, Tanmay
Abstract: Diverse mechanisms exist in Mycobacterium tuberculosis for adaptation to stresses leading to its persistence in the hostile environment of macrophages. Small RNA (sRNA)-mediated regulatory mechanisms have been scarcely explored in M. tuberculosis . MTS1338, a sRNA present only in pathogenic mycobacteria, was discovered to be highly abundant during infection and significantly contributes to host-pathogen interaction. A variety of stresses have been implicated for its accumulation. Herein, we showed that MTS1338 is an oxidative stress induced sRNA, which promotes the detoxification of reactive oxygen species (ROS) under oxidative stress. Current study identified a new role of MTS1338 in M. tuberculosis under oxidative stress. Highlights: MTS1338 is a novel oxidative stress induced small RNA in M. tuberculosis. MTS1338 overexpression in M. tuberculosis is nontoxic. MTS1338 abundance under oxidative stress promotes detoxification of reactive oxygen species.